Village assistance towards independence in safe drinking water and healthy food - sulaiman hamzani; Syarifudin A; Niken Pratiwi (UPPM Poltekkes Kemenkes Banjarmasin, 2026)
Village in Banjar Regency faces serious challenges in providing safe drinking water to residents living along the banks of the Martapura River. Pollution from domestic and agricultural waste, coupled with limited resources, has led to limited access to safe drinking water, which increases public health risks. This community service activity aims to improve access to and quality of safe drinking water and encourage changes in community behavior regarding the provision of healthy food. The implementation method includes mapping community water sources, training in water treatment and healthy food processing, and developing a community-based drinking water supply plan involving village heads and local cadres. The results of the activity show a significant increase in access to safe drinking water from 10 families to 50 families. In addition, the